The True Nature of Tauhid and Its Relation to The Problem of the Muslim in the World - Gunawan Adnan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
Tauhid is an essential element in the Islamic framework of a Muslim. Tauhid is both the Alpha and Omega of Islam. Everything born in the name of Islam should reflect the divine will. Consequently, the doctrines and practices (worship) in Islam should both represent and demonstrate this fundamental meaning. Sharia, in essence, is the operational aspect of the concept of tauhid, so there should be no contradiction between tauhid and sharia. This article examines various forms and levels of understanding the concept of tauhid, linked to the issues facing the Muslim community as an effort to find appropriate solutions to the challenges faced by the community in the midst of global competition.